(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Endometriosis is a chronic and recurrent disease characterized by the presence and proliferation of functional endometrial glands and stroma outside the uterine cavity. GnRH analogues are currently one of the most widely used medical therapies for endometriosis. Objective:This study assesses the role of zoladex (goserelin acetate depot) for patients with recurrent endometriosis after surgical treatment. Methods: A descriptive follow up study of 20 women with recurrent endometriosis after surgery were arranged to receive Goserelin acetate (Zoladex) one month depot administered subcutaneously monthly for a period of six months followed by one year follow up in AL- Karama Teaching Hospital -Wasit Governorate/ Iraq from May 2008 until May 2010. Results:Ninety percent of patients showed symptomatic improvement, ultrasound improvement achieved in 80%, recurrence rate of 20% within one year after stopping treatment and none of the patients required surgical interference during the period of the study. Conclusions:Our results support the beneficial role of Goserelin acetate (3.6 mg) month depot administered subcutaneously in the treatment of recurrent endometriosis after surgery. Keywords :Endometriosis, GnRH analogues, Goserelin acetate